2002
DOI: 10.1007/bf02504998
|View full text |Cite
|
Sign up to set email alerts
|

Motivating students at a distance: The case of an international audience

Abstract: Distance education is rapidly becoming an increasingly important -and even preferredmethod of instructional delivery for many educational contexts. In spite of the many student benefits surrounding distance learning programs, however, a great number of distance learning courses suffer from extremely low student completion rates when compared to their traditional classroom-based counterparts. Although it may be tempting to point to instructional content and methods as the source of low distance learning complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 3 publications
0
27
0
5
Order By: Relevance
“…With new resources, images, videos, storyboards and technologies increasingly applied into web-based instruction design, the analysis of learner experience has to take learners' cognitive, affective and even physical behaviours into consideration in order to address the complexity of inter-activities among the factors of online dynamics. We emphasize evaluating students' attitudes toward course design (Visser, Plomp, Arimault, & Kuiper, 2002) and discovering how affect factors and outcome bound behaviours are related in online courses, and additionally, how the difference in course design and individual difference might have affected these factors.…”
Section: Introductionmentioning
confidence: 99%
“…With new resources, images, videos, storyboards and technologies increasingly applied into web-based instruction design, the analysis of learner experience has to take learners' cognitive, affective and even physical behaviours into consideration in order to address the complexity of inter-activities among the factors of online dynamics. We emphasize evaluating students' attitudes toward course design (Visser, Plomp, Arimault, & Kuiper, 2002) and discovering how affect factors and outcome bound behaviours are related in online courses, and additionally, how the difference in course design and individual difference might have affected these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that high dropout rates can be improved through blended instruction (Rowley et al 2002), motivational messages (Visser et al 2002) as well as other means of student support to improve performance and retention. Thayer, Newman and McClain (1994:910) explain that emotion is related to motivation as people tend to do things they hope will lead to happiness and satisfaction, or as Bradley (2000:602) describes it, "both emotion and motivation are fundamentally related to action".…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in looking at components of motivation in a group of international distance education students, Visser, Plomp, Amirault and Kuiper (2002) use the ARCS model (attention, relevance, confidence and satisfaction) to find that attempts to personally customize motivational messages for students was time-consuming and no more effective than collective messages. Gunawardena et al (1996) used Kolb's Learning Style Inventory to characterize the learning styles of adult learners in Open University students in Sri Lanka.…”
Section: Culture and Educational Psychology Constructsmentioning
confidence: 99%